Non-cognate translation priming in masked priming lexical decision experiments: a meta-analysis - Wen, Yun; van Heuven, Walter J.B. (Springer, 2017)
The masked translation priming paradigm has been widely used in the last 25 years to investigate word processing in bilinguals. Motivated by studies reporting mixed findings, in particular for second language (L2) to first language (L1) translation priming, we conducted, for the first time in the literature, a meta-analysis of 64 lexical decision experiments across 24 studies to assess the effect sizes of L1-L2 and L2-L1 non-cognate translation priming effects in bilinguals. Our meta-analysis also investigated the influence of potential moderators of translation priming effects. The results provided clear evidence of significant translation priming effects for both directions, with L1-L2 translation priming significantly larger than L2-L1 translation priming (i.e., effect size of 0.86 vs. 0.31). The analyses also revealed that L1-L2 translation effect sizes were moderated by the interval between prime and target (ISI), whereas L2-L1 translation effect sizes were modulated by the number of items per cell. Theoretical and methodological implications of this meta-analysis are discussed and recommendations for future studies are provided.